2005
DOI: 10.1097/01.blo.0000167832.47464.22
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Provides Superior Skin Decontamination in Foot and Ankle Surgery

Abstract: Therapeutic study, Level I-1a (significant difference). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
103
4
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 18 publications
11
103
4
1
Order By: Relevance
“…Other comorbidities associated with increased risk of postoperative infection include obesity, malnutrition, tobacco use, and immunosuppressive medication [11,21,43,45]. Another potential cause for greater concern for surgical site infections after foot and ankle surgery is the persistent colonization of the forefoot despite preoperative preparation [7,12,30,47,48,63,65]. Ostrander et al [47] reported positive cultures after application of surgical preparation solution in 125 patients, ranging from 23% to 98% from the hallux nailfold and second and third web spaces, compared with 10% to 35% from the anterior tibia control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other comorbidities associated with increased risk of postoperative infection include obesity, malnutrition, tobacco use, and immunosuppressive medication [11,21,43,45]. Another potential cause for greater concern for surgical site infections after foot and ankle surgery is the persistent colonization of the forefoot despite preoperative preparation [7,12,30,47,48,63,65]. Ostrander et al [47] reported positive cultures after application of surgical preparation solution in 125 patients, ranging from 23% to 98% from the hallux nailfold and second and third web spaces, compared with 10% to 35% from the anterior tibia control.…”
Section: Discussionmentioning
confidence: 99%
“…Ostrander et al [47] reported positive cultures after application of surgical preparation solution in 125 patients, ranging from 23% to 98% from the hallux nailfold and second and third web spaces, compared with 10% to 35% from the anterior tibia control. Multiple studies have reported postpreparation forefoot cultures ranging from 0% to 84%, most reporting greater than 50% [7,12,28,30,48,63,65]. Studies also have shown intraoperative forefoot recolonization [12,63,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The superior clinical efficacy of chlorhexidine-alcohol in our study correlates well with previous microbiologic studies showing that chlorhexidine-based antiseptic preparations are more effective than iodine-containing solutions in reducing the bacterial concentration in the operative field for vaginal hysterectomy [3] and foot-and-ankle surgery. [4,5] Although the use of flammable alcohol-based products in the operating room poses the risk, though small, of fire or chemical skin burn, no such adverse events occurred in this study or the other studies. [3,5] Chlorhexidine is a cationic biguanide that binds to the negatively charged surface of bacterial cell wall leading to alteration in permeability, which leads to leakage of cytoplasmic contents and finally cell death.…”
Section: Discussionmentioning
confidence: 59%
“…[4,5] Although the use of flammable alcohol-based products in the operating room poses the risk, though small, of fire or chemical skin burn, no such adverse events occurred in this study or the other studies. [3,5] Chlorhexidine is a cationic biguanide that binds to the negatively charged surface of bacterial cell wall leading to alteration in permeability, which leads to leakage of cytoplasmic contents and finally cell death. [6] The residual effect; defined as the long-term antimicrobial suppressive activity; of chlorhexidine gluconate, is prolonged (at least 6 h) while that of povidone-iodine is minimal.…”
Section: Discussionmentioning
confidence: 59%